Disappearance on Display: Vanished Torah Arks in Medieval Synagogues and Their Presentation - Maria Stürzebecher (Arts, 2020)
In planning the museum in the medieval Synagogue in Erfurt more than 10 years ago, there was one big problem: the building had gone through many changes over the centuries, which wiped out almost all traces of the synagogue’s use. The Bimah was destroyed, presumably during the pogrom on 21 March 1349. By converting the former synagogue into a warehouse (following the pogrom), a big gateway was inserted into the eastern wall, at the place of the former Torah Ark. Only the light cornice is still recognizable on the synagogue’s walls. To find an adequate solution for displaying the vanished Torah Ark in the Old Synagogue in Erfurt, we compared examples in other locations in Europe, suggesting the presentation eventually chosen for the Old Synagogue of Erfurt.